Implementasi Pendidikan Agama Islam dengan Metode Hybrid Berbasis IT di SMP Islam Al Azhar 50 Sragen dan SMP Islam AL Abidin Surakarta - Riyas Agung Pangestu; Muhammad Wildan Shohib; Mutoharrun Jinan (Pusat Riset dan Inovasi Nasional, 2025)
The rapid advancement of technology and globalization presents challenges for the education sector, particularly in shaping students' character and social skills. Islamic education in the digital era must adapt to learning methods that not only focus on cognitive development (hard skills) but also emphasize the enhancement of soft skills, which include social, emotional, and spiritual aspects. The hybrid IT-based learning method emerges as an innovative approach that integrates face-to-face learning with digital technology to enhance the effectiveness of Islamic education. This study aims to analyze the implementation of the hybrid IT-based method in shaping students' soft skills at SMP Islam Al Azhar Sragen and SMP Islam Al Abidin Surakarta, as well as to identify the supporting and inhibiting factors in its implementation. This research employs a qualitative descriptive approach using a comparative study method, with data collected through observations, interviews, and documentation. The findings indicate that the implementation of hybrid IT-based learning significantly contributes to the development of students' soft skills, such as communication, teamwork, independence, leadership, critical thinking, and responsibility. Key supporting factors include technological infrastructure, teachers’ readiness to utilize digital media, and a school environment that upholds Islamic values. On the other hand, inhibiting factors include limited technology access for some students, low digital literacy among students and parents, and challenges in objectively assessing soft skills. This study provides new insights into the effectiveness of the hybrid IT-based method in Islamic education and offers strategic recommendations for its optimization. The findings are expected to serve as a reference for Islamic schools in developing learning models that align with modern educational advancements while preserving Islamic values in character building.